3071 Cell Survival in Corneal Endothelial Dystrophies - Rajalekshmy Shyam; Diego Ogando; Moonjung Choi; Joseph Bonanno (Journal of Clinical and Translational Science, 2019)
OBJECTIVES/SPECIFIC AIMS: Purpose - The goal of this study is to understand how loss of the membrane protein SLC4A11 alters endothelial cell metabolism thereby producing Corneal Endothelial Dystrophy. Studies from our lab indicated that glutamine-dependent mitochondrial dysfunction is one of the outcomes of SLC4a11 loss. In the current study, we ask if autophagy and mitophagy pathways and the signaling pathways that regulate these processes are altered in SLC4a11 KO cells. METHODS/STUDY POPULATION: Methods – Immortalized mouse WT and SLC4a11 KO cell lines were incubated in DMEM with and without 0.5mM glutamine for 6 hours. In order to assess mitophagy, cells were stained using Lysotracker Red and Mitotracker Green. Colocalization co-efficients of red and green channels were obtained for at least 35 cells using Zeiss-Zen Pro software. Student’s t-test was used to determine statistical significance. For Western Blots, antibodies against LC3b, AMPK, pAMPK, and b-actin were used to examine autophagy flux and potential signaling pathways that regulate autophagy. RESULTS/ANTICIPATED RESULTS: Results – In the presence of glutamine, the colocalization co-efficient of Lysotracker Red and Mitotracker Green channels was significantly increased in KO cells (0.74 ±0.18) relative to WT (0.58±0.20) with a p-value ≤0.0024. In the absence of glutamine, the colocalization co-efficient was reversed, for KO cells 0.54 ±0.14 and for WT cells 0.77±0.0.16 with a p-value ≤0.0001, suggesting increased mitophagy by glutamine in KO cells. Western Blots indicated that glutamine increased autophagy flux, as indicated by increased levels of LC3b following bafilomycin A treatment in KO cells. Concomitantly, there was an increase in pAMPK/AMPK levels suggesting a potential mechanism for increased mitophagy. DISCUSSION/SIGNIFICANCE OF IMPACT: Conclusion and Future studies –Our data indicates enhanced mitophagy as well as autophagy in SLC4a11 KO cells. Future studies will determine whether these processes regulate cell survival in mouse models of corneal endothelial dystrophies.